1949
DOI: 10.1021/ja01173a084
|View full text |Cite
|
Sign up to set email alerts
|

Butadiene from Ethanol. Reaction Mechanism

Abstract: The manufacture of butadiene from ethanol by the American two-step process developed by Car-bide and Carbon Chemicals Corporation3•4 and operated by that organization and by Koppers Company, Inc., comprised (1) dehydrogenation of ethanol to acetaldehyde followed by (2) catalysis of acetaldehyde-ethanol to produce butadiene. This paper discusses the mechanism of the second step, ih which a mixture of approximately 69 wt. % of ethanol, 24 wt. % of acetaldehyde and 7 wt. % of water was passed over a 2% Ta20s-98% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 0 publications
1
46
0
1
Order By: Relevance
“…Fig. 11 The ion intensity of BD with mole ratio of feed In the experiment of impulse response, the mixed ethanol-acetaldehyde feed leading to BD formation, as reported by the Soviet and American workers [7]. So the ethanol was fed after the acetaldehyde.…”
Section: The Drifts Of Acetaldehyde Reaction On the Mgo/sio 2 Catalystmentioning
confidence: 77%
See 1 more Smart Citation
“…Fig. 11 The ion intensity of BD with mole ratio of feed In the experiment of impulse response, the mixed ethanol-acetaldehyde feed leading to BD formation, as reported by the Soviet and American workers [7]. So the ethanol was fed after the acetaldehyde.…”
Section: The Drifts Of Acetaldehyde Reaction On the Mgo/sio 2 Catalystmentioning
confidence: 77%
“…At the mechanistic point of view, the one-step of ethanol to BD is extremely complicated and is still a debatable subject. Gorin [7] suggests that the reaction mechanism may be represented as follows:…”
Section: Introductionmentioning
confidence: 99%
“…First, the supposed intermediate acetaldol is seldom detected amongst the products of the reaction, arguably due to its facile dehydration. Second, the engineers at Union Carbide Corporation have reported that acetaldol was converted back to acetaldehyde when fed together with ethanol into a reactor packed with a 2% Ta/SiO2 catalyst without producing butadiene [15]. This suggests that …”
Section: The Kagan Mechanismmentioning
confidence: 99%
“…(8)); and dehydration of crotyl alcohol to obtain 1,3-butadiene (Eq. (9)) [Makshina, 2012;Jones, 2011;Kvisle, 1988;Toussaint, 1947;Jones, 1949]. Nevertheless, to obtain the true kinetic behavior for this complex system of reactions it is necessary to conduct further studies involving the identification and monitoring of intermediate species of the reaction by analytical techniques in situ.…”
Section: Characterizationmentioning
confidence: 99%